The 2024–2025 Pertussis outbreak in children in Chengdu: A large-scale retrospective cross-sectional study - Xu Zhang; Hongjia Chen (PLoS ONE, 2026)
Objective To characterize the epidemiological features of pertussis among pediatric patients tested by polymerase chain reaction (PCR) at a tertiary children's hospital in Chengdu from May 2024 to April 2025, with particular emphasis on temporal variation and age distribution, to inform regional prevention strategies. Methods This retrospective cross-sectional study included 19,084 pediatric patients who underwent PCR testing for Bordetella pertussis . Multivariable logistic regression and subgroup analyses were used to examine associations between PCR positivity and season, age group, sex, and visit type. Results The overall PCR positivity rate was 20.47% (3,905/19,084). Summer had the highest positivity rate (25.62%) and accounted for the majority of positive cases (67.12%, 2,621/3,905), followed by spring (21.50%; 23.58% of cases, 921/3,905). The monthly number of positive cases peaked in June 2024 (n = 1,078). School-aged children (6 to <12 years) represented the largest proportion of positive cases (56.72%, 2,215/3,905) and had significantly higher PCR positivity than other age groups (χ² = 1098.21, df = 4, P < 0.001). In multivariable analysis, school-aged children had higher odds of PCR positivity than adolescents (adjusted OR = 1.55, 95% CI 1.23–1.95). No significant association with sex was observed. Outpatients showed higher PCR positivity than inpatients (21.41% vs. 13.66%; crude OR = 1.72, 95% CI 1.52–1.95, P < 0.001). The outpatient advantage was most pronounced in spring (crude OR = 1.95) and summer (crude OR = 1.44), with a significant interaction by season ( P = 0.013). Conclusion This hospital-based study identified a substantial burden of PCR-confirmed pertussis among symptomatic children in Chengdu during the study period, with a prominent peak from May to July 2024 and the highest positivity among school-aged children. These findings may partly reflect waning vaccine-induced immunity and increased social contact in school settings, and support strengthened surveillance, timely PCR testing, and targeted pertussis prevention strategies for school-aged children.